2014
DOI: 10.1007/s11011-014-9491-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione metabolism enzymes in brain and liver of hyperphenylalaninemic rats and the effect of lipoic acid treatment

Abstract: Phenylketonuria (PKU) is a disorder caused by a deficiency in phenylalanine hydroxylase activity, which converts phenylalanine (Phe) to tyrosine, leading to hyperphenylalaninemia (HPA) with accumulation of Phe in tissues of patients. The neuropathophysiology mechanism of disease remains unknown. However, recently the involvement of oxidative stress with decreased glutathione levels in PKU has been reported. Intracellular glutathione (GSH) levels may be maintained by the antioxidant action of lipoic acid (LA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Furthermore, Moraes et al (2014) reported that LA could prevent the reduction in GPx, GR activities, and the reduced GSH level without any changes in the GST activity in hyerphenylalaninemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Moraes et al (2014) reported that LA could prevent the reduction in GPx, GR activities, and the reduced GSH level without any changes in the GST activity in hyerphenylalaninemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…OLs and its precursors are sensitive to alterations in redox homeostasis (Brill, Scheuer, Bührer, Endesfelder, & Schmitz, 2017;Takase et al, 2018). Several reports indicate that oxidative stress is implicated in the pathophysiology of PKU, as demonstrated in animal HPA models (Fernandes et al, 2010;Lu et al, 2011;Mazzola et al, 2011;Moraes et al, 2014;Simon et al, 2013) and in samples from PKU patients (Huemer et al, 2012;Item et al, 2017;Okano & Nagasaka, 2013;Sitta et al, 2009Sitta et al, , 2011. The interplay between oxidative stress and bioenergetics dyshomeostasis has been associated with myelin defects.…”
Section: Cn S Demyelinati On In Pkumentioning
confidence: 99%
“…Some studies showed an increase of lipoperoxidation markers (Sanayama et al 2011) and DNA damages (Sitta et al 2009), or a reduction of various antioxidant compounds, especially selenium, coenzyme Q10, or antioxidant system of glutathione (Menzel et al 1983;Sitta et al 2006;Sanayama et al 2011). Decrease of antioxidant compounds was also observed in animal and in vitro models of PKU (Ercal et al 2002;Fernandes et al 2010;Mazzola et al 2011;Moraes et al 2014). Imbalance in redox homeostasis in PKU is now admitted, but its link with metabolic disturbances observed in the disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%